LIGHTWEIGHT HIGH STRENGTH CONCRETE WITH EXPANDED POLYSTYRENE BEADS - Subhan, Tengku Fitriani L. (MEKTEK, 2006)
This paper is a literature study about lightweight high strength concrete by incorporating expanded polystyrene beads. Basically polystyrene is disposal material from packaging industry. However, after being processed in a special manner, polystyrene can be expanded and used as lightweight concrete making material. Therefore, the use of expanded polystyrene beads in concrete is not only beneficial for engineering studies but also provide solution for the environmental problem